A roadmap for evidence-based insurance development for Nigeria’s farmers - Hansen, James; Hellin, Jonathan; Rose, Goslinga; Araba, Debisi (2017)
In 2014, Nigeria’s Federal Ministry of Agriculture and Rural Development (FMARD) proposed a major expansion of agricultural insurance in the context of other reforms to the agricultural sector, and as part of the implementation of its National Agricultural Resilience Framework (NARF). This report is designed to inform development of inclusive insurance for Nigeria’s agriculture sector, and is offered as a contribution to the NARF. It is an outcome of a consultative process that began in September 2014 between FMARD and the CGIAR research program on Climate Change, Agriculture and Food Security (CCAFS). By overcoming the problems of moral hazard, adverse selection, and resulting high transaction costs and processing delays that have plagued indemnity-based agricultural insurance, index-based insurance makes it feasible to insure millions of smallholder farmers. Well-designed index insurance can achieve specific risk objectives such as protecting farmers’ livelihoods in the face of major climate shocks, and promoting farmers’ livelihoods by overcoming barriers to adoption of improved agricultural technologies and practices, and access to market opportunities. Reviews of index-based agricultural insurance initiatives have identified several success factors that are relevant to the situation in Nigeria. First, successful initiatives have been designed to unlock particular opportunities for farmers that were previously constrained by particular risks. Second, initiatives are most successful when they are driven by demand and responsive to farmer input. Third, successful initiatives have invested in the capacity of a range of local stakeholders. Fourth, investments in data systems, and in science-based index development, have helped address the challenges of data poverty and basis risk. Fifth, successful index insurance requires an enabling regulatory environment. Finally, successful initiatives involve multi-stakeholder partnerships, and often public-private partnerships. A strategy for expanding insurance for Nigeria’s smallholder farmers must address challenges that include: limited and asymmetric information; crowding out by post-disaster relief efforts; limited access to reinsurance markets; lack of insurance culture; and inadequate regulatory environments. The development of effective market-based agricultural insurance, requires government support in five key areas: data systems; awareness and capacity building; facilitating international risk pooling; “smart” subsidies; and an enabling policy environment. Three immediate priorities are identified: (a) creating a regulatory environment that makes it attractive for insurance companies to enter the market; (b) developing a public-private partnership that incentivizes and supports companies to develop innovative products and services for the agriculture sector; and (c) progressively expand implementation through well-designed pilots, evaluation and learning processes. The organizations that have been involved or consulted in the process leading to this report offer relevant expertise.